2020
DOI: 10.3390/su12239798
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement and Failure in University Studies: Motivational and Emotional Factors

Abstract: Universities are committed to offering quality education; however, a high rate of academic failure is often observed in the first year of studies. Considering the impact that motivation and emotional aspects can have on students’ commitment to study and therefore on their academic performance, achievement, and well-being, this study aims to identify the factors associated with academic success or failure in 1071 students entering the National Polytechnic School (Quito, Ecuador). The data were compiled from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Theoretically our findings add to the literature examining the role of positive psychology in general and emotional resources in particular within a context that is often viewed as‚ cognitive' in nature. The model we propose underlines the relevance of emotional and social factors in higher education environments (Gilar-Corbi et al, 2020;Jaeger & Eagan, 2007). It also suggests a conceptual link between individual level emotional factors and social level behavior and resources (at least at the perceived level).…”
Section: Theoretical Contributionmentioning
confidence: 71%
“…Theoretically our findings add to the literature examining the role of positive psychology in general and emotional resources in particular within a context that is often viewed as‚ cognitive' in nature. The model we propose underlines the relevance of emotional and social factors in higher education environments (Gilar-Corbi et al, 2020;Jaeger & Eagan, 2007). It also suggests a conceptual link between individual level emotional factors and social level behavior and resources (at least at the perceived level).…”
Section: Theoretical Contributionmentioning
confidence: 71%
“…Student performance is not only determined by the assessment method. Studies and meta-analyses in the university context suggest that performance is affected by a large number of variables such as emotional attention, motivational self-efficacy, prior academic performance, student motivation, goal-directed learning strategies, and teaching style and practices such as the use of feedback [39,40]. Evidence also shows an association between learning styles and performance [4,17,22,41].…”
Section: Assessment Method Academic Performance and Learning Dimensionsmentioning
confidence: 99%
“…Over the last decade, the Organization for Economic Co-operation and Development has reported that approximately one-third of students entering higher education will not graduate (OECD, 2013). The majority of students' withdrawals occur during the first year of studies (Hultberg et al, 2008;Webb and Cotton, 2018;Gilar-Corbi et al, 2020), a year that is considered extremely critical for the overall success in undergraduates' studies (Perry et al, 2001). Thus, this initial phase of higher education sets the stage for either to earn a degree or dropout from university (Tinto, 1993;Díaz Mujica et al, 2019;Nicoletti, 2019) and still remains a major political concern in Europe (Vossensteyn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%